Measurement of Event-Related Brain Potentials (ERP) Amplitude and Latency Based on Digital Stochastic Measurement over Interval - Novakovic, Djordje; Sovilj , Platon; Petrovic, Nikola; Milovanovic, Milan; Makal, Jaroslaw; Walendziuk, Wojciech (Elektronika ir Elektrotechnika, 2020)
In this paper, the measurement of event-related brain potentials (ERP) amplitude and latency based on digital stochastic measurement over interval (DSMI) method are described. Different variations of the measurement system are considered. It was found that measurement errors of amplitude increase with the reduction of the examination time. However, the measurement errors for ERP peak latency remain relatively small. This makes the system useful for practical implementations when the latency is the most interesting parameter and requirements for a short measurement time are of high priority.